Synthesization and characterization of porous adsorbents for energy storage and utilization - Ong, Andrea Sing Yee (Nanyang Technological University, 2022)
Metal-Organic Frameworks (MOFs), also known as porous coordination networks, are a type of sophisticated materials that are made up of organic linkers and metal ions. In nature with significant porosity, MOFs have evolved into an extensive group of crystalline materials. Unlike other porous materials like zeolites and activated carbon, MOFs are a class of materials with several advantages such as ultra-low densities, thermal stability, discrete ordered structure, ease of synthesis, large internal surface area and broad-spectrum of properties that are suitable for chemical and physical applications. These distinguishing characteristics prompted a never-ending research for new porous materials. MOFs exemplifies the elegance of chemical structures and the importance of combining organic and inorganic components on a fundamental level. Several definitions for the term MOF have been proposed by researchers from all around the world. In this report, a variety of MOFs are presented primarily including MIL-101 (Cr) and its various permutations. The experimental methods for synthesizing MOFs are also explained and discussed. For this project, ionic liquids are being impregnated into the pores of MOFs to analyze the variations in pore sizes which can also improve the adsorption capacity. Scanning electron microscopy (SEM) and Thermogravimetric analyzer (TGA) is used to evaluate the characterizations of the MOFs. The SEM is used to examine structural morphology whereas the TGA is used to determine thermal stability. The results show that the synthesis process for the MOFs is successful as the color for the powdered form of MOFs such as MIL-101 (Cr) and HKUST-1 are of expected outcome for the firsthand result before proceeding to utilize Thermogravimetric Analysis (TGA) and Scanning Electron Microscopy (SEM) to obtain a more detailed result. The presence of ionic liquid in MIL-101 MOFs results in an increment of adsorption capacity and when comparing it with the original MIL-101 (Cr), the thermal stability of its materials is maintained. The proposed adsorbents are suitable for adsorption assisted heat transformations such as cooling, heat pump thermal energy storage or potential gas storage applications.